On-chip mid-infrared thermal emitter for filter-free gas sensing - Ma, Yixuan (Nanyang Technological University, 2020)
Optical gas sensing system is developing in recent years. Metamaterial can replace the filter in gas sensor. and with the integration of MEMS, it is possible to set up low-cost, CMOS compatible gas sensor. With changing dimension and shape of metamaterial resonator, different gases can be recognized from gas mixture separately. By testing metamaterials with different shapes, the conclusion is concluded that cross-shaped resonator is the most suitable one for filtering with high quality factor. With adjusting the cross-shaped material unit cell, it can detect many gases with resonance peak in mid-IR region. One of the applications of this metamaterial integrated gas sensor is detecting vehicle emission gases. With smaller volume and cheaper price, it still has great research value.